ANALYSIS OF OCCUPATIONAL STRESS AS RELATED TO SOME PSYCHOSOCIAL AND CAREER VARIABLES OF NIGERIAN UNIVERSITY TEACHERS (1994)
This study investigated occupational stress as related to psychosocial variables of job satisfaction and psychological well-being of teachers in the first generation Nigerian Universities. Also the study assessed the differences in occupational stress experienced by the teachers with respect to career variables such job status and years of teaching experience as well as biographical characteristics namely, age and sex. The research method was a cross-sectional survey design. Cluster sampling technique was used to select teachers in the first generation Nigerian universities. A total of 300 university teachers responded to the Teacher Stress and Job Satisfaction Questionnaire as well as the General Health Questionnaire. Descriptive statistics were used to summarise the data. Multiple regression, chi-square, t-test and Analysis of Variance (ANOVA) were used to test the hypotheses at .05 level of significance. Scheffe post-hoc test was used to detect differences among groups where ANOVA was found significant. The results show that an overwhelming majority of the teachers (67.0%) were experiencing moderate levels of occupational stress while 15.0% and 18.0% were experiencing low and high levels of stress respectively. Despite this, 97.0% of the teachers reported moderate to high levels of job satisfaction with only 3.0% reporting low job satisfaction. Also a majority of the teachers (94.0%) reported moderate to high levels of psychological well-being. The reason for the findings are not clear. but it could be that the teachers have learnt to cope with the stressors encountered in the course of their work. Possibly, it could that the reported high levels of job satisfaction may have helped to moderate or reduce the impact of stress on the teachers' health. Regression analysis revealed a positive and significant relationship between occupational stress and job dissatisfaction (r=.43; P < .001); between occupational stress and psychological symptoms (r = .35; P < .001); and between job dissatisfaction and psychological symptoms (r = .45; P < .001). These findings are consistent with previous studies on teacher stress. Furthermore, there were no significant differences in total occupational stress levels with respect to age, sex and years of teaching experience. However, there was a significant difference in stress levels experienced by the teachers with respect to job status. Professors and Readers reported the lowest levels of stress followed by Senior Lecturers with junior lecturers-experiencing the most stress. The study identified the major sources of occupational stress among the Nigerian university teachers. Shortage of teaching materials, poor working conditions, heavy workload, time pressure, overcrowded classrooms, low salary and unfavourable conditions of service ranked accordingly as the most significant causes of stress. Finally, the present study indicated that occupational stress, job satisfaction and psychological health are closely related and that greater stress leads to low job satisfaction and some degree of psychological dysfunction. Thus occupational stress has negative effects on teachers' health and well-being. Moreover the results support the view in literature that teaching is a satisfying but a demanding and stressful occupation. Based on the findings of this study recommendations were made on how to reduce occupational stress and improve the health and quality of life of university teachers.